Heat Shock Protein-70 Levels Are Associated With a State of Oxidative Damage in the Development of Bronchopulmonary Dysplasia - Hsiao, Chien-Chou; Lee, Cheng-Han; Yang, Rei-Cheng; Chen, Jia-Yuh; Su, Tzu-Cheng; Chang, Yu-Jun; Lin, Ching-Yuang; Tsai, Yi-Giien (Frontiers in Pediatrics, 2021)
Background: Heat shock protein-70 (Hsp-70) has cytoprotective effects against oxidative stress-induced airway injury. The study aimed to investigate Hsp-70 and oxidative stress marker with 8-hydroxy-2’-deoxyguanosine (8-OHdG) from tracheal aspirates (TA) in very low birth weight (VLBW) preterm infants following development bronchopulmonary dysplasia (BPD). Methods: This birth cohort study enrolled 109 VLBW preterm infants, including 32 developed BPD. Hsp-70 and 8-OHdG concentrations from TA were measured by immunoassay. Apoptosis from TA epithelial cells on days 28 after birth was measured using Annexin V staining assay. Results: Hsp-70 and 8-OHdG levels in TA fluid were persistently increased from first to 28th day of life in BPD group. Multiple linear regression analysis demonstrated that BPD was significantly associated with gestational age, respiratory distress syndrome, TA Hsp-70 and 8-OHdG levels on post-natal day 28. The TA Hsp-70 positively correlated with 8-OHdG levels on the first (r = 0.47) and 28th day of life (r = 0.68). Incubation of primary epithelial cells derived from patient TA with recombinant Hsp-70 decreased hydrogen peroxide-induced epithelial cell death. Conclusions: We conclude that Hsp-70 inhibited oxidant-induced apoptosis may offer a new biomarker and strategy to treat lung injuries linked to oxidative stress in BPD.